Metals and Arsenic in Water Supply for Riverine Communities Affected by the Largest Environmental Disaster in Brazil: The Dam Collapse on Doce River - de Carvalho, Gabriel Oliveira; Pinheiro, André de Almeida; de Sousa, Dhoone Menezes; Padilha, Janeide de Assis; Souza, Juliana Silva; Galvão, Petrus Magnus; Paiva, Thaís de Castro; Freire, Aline Soares; Santelli, Ricardo Erthal; Malm, Olaf; Torres, João Paulo Machado (Orbital: The Electronic Journal of Chemistry, 2018)
Considered the worst environmental disaster in Brazilian history, the collapse of Samarco dam directly affected the Doce river. Inhabitants living along the river who relied mainly on Doce river’s water supply for agriculture and human consumption faced risk from the mining residue exposure. This study aimed to investigate the disaster’s impact on small family farmers living in Minas Gerais and Espírito Santo States by water elemental quantification and evaluate the potential pathways of contamination by survey. In July 2016, 48 water points - including well, river and public distributed water - of 3 cities (Belo Oriente, Governador Valadares and Colatina) were sampled for determination of As, Cd, Cr, Cu, Fe, Hg, Mn, Ni, Pb, Sn and Zn elements. Ninety-eight percent of the inhabitants interviewed related Doce river water usage before the tragedy for diversified purposes, while only thirty-six per cent used it after the disaster, mainly for irrigation. Fe and Mn presented concentrations above the Brazilian legislation for drinking water and irrigation in all locations, but not in all samples. Pb concentration was above the drinking water legislation in one location. All the other elements concentrations were within safe limits. Colatina, the farthest city from the dam, presented the highest values, followed by Governador Valadares and Belo Oriente. DOI: http://dx.doi.org/10.17807/orbital.v10i4.1081